„Mich interessierten kostengünstige Alternativen zu Citavi“: Über den Fortbildungsworkshop „Literaturverwaltung im Fokus“ im Rahmen der AGMB-Tagung 2012 [“I was interested in competitive alternatives to Citavi”: About the workshop “Reference Management at the focal point”, held at the AGMB-Conference 2012] - Stöhr, Matti (GMS Medizin – Bibliothek – Information, 2012)
[english] A two hour taking workshop on reference management, covering several software types, library services and more were part of the program at the AGMB-Conference 2012 in Aachen. This article is dealing less with the offered workshop contents itself. Moreover the attendees’ perspective is described. With an email-based survey the following main question wanted to be answered: Was the workshop fruitful for the participants? [german] Zum Programm der AGMB-Tagung 2012 in Aachen gehörte u.a. der zweistündige Fortbildungsworkshop „Literaturverwaltung im Fokus – Softwaretypen, bibliothekarische Services und mehr“. Im Beitrag werden weniger die referierten Workshopinhalte beschrieben, als vielmehr die Perspektive der Teilnehmerinnen und Teilnehmer anhand einer eMail-basierten Umfrage vorgestellt. Die Kernfrage lautet hierbei: War der Workshop für sie gewinnbringend?